(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article discusses the need to develop the market for appraisal services, which is one of the important infrastructures of a market economy. The digitalization processes taking place today all over the world, the introduction of artificial intelligence in various fields and their impact on valuation activities are revealed. The prospects and practical problems of digitalization of appraisal activities in the Republic of Uzbekistan and the introduction of artificial intelligence in this area are highlighted.